Combining Phi6 as a surrogate virus and computational large‐eddy simulations to study airborne transmission of SARS‐CoV‐2 in a restaurant. (27th November 2022) - Oksanen, Lotta; Auvinen, Mikko; Kuula, Joel; Malmgren, Rasmus; Romantschuk, Martin; Hyvärinen, Antti; Laitinen, Sirpa; Maunula, Leena; Sanmark, Enni; Geneid, Ahmed; Sofieva, Svetlana; Salokas, Julija; et al.
Abstract: COVID‐19 has highlighted the need for indoor risk‐reduction strategies. Our aim is to provide information about the virus dispersion and attempts to reduce the infection risk. Indoor transmission was studied simulating a dining situation in a restaurant. Aerosolized Phi6 viruses were detected with several methods. The aerosol dispersion was modeled by using the Large‐Eddy Simulation (LES) technique. Three risk‐reduction strategies were studied: (1) augmenting ventilation with air purifiers, (2) spatial partitioning with dividers, and (3) combination of 1 and 2. In all simulations infectious viruses were detected throughout the space proving the existence long‐distance aerosol transmission indoors. Experimental cumulative virus numbers and LES dispersion results were qualitatively similar. The LES results were further utilized to derive the evolution of infection probability. Air purifiers augmenting the effective ventilation rate by 65% reduced the spatially averaged infection probability by 30%–32%. This relative reduction manifests with approximately 15 min lag as aerosol dispersion only gradually reaches the purifier units. Both viral findings and LES results confirm that spatial partitioning has a negligible effect on the mean infection‐probability indoors, but may affect the local levels adversely. Exploitation of high‐resolution LES jointly with microbiological measurements enables an informative interpretation of the experimental results and facilitates a more complete risk assessment.